Letter from Max Bredig to Georg Bredig, November 3, 1936 - Bredig, Max Albert (1936)
Max Albert Bredig (1902-1977) writes to his father, Georg Bredig (1868-1944). Max reports his discoveries related to the formation of metal carbides.